2020
DOI: 10.1038/s41598-020-72075-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic profiling reveals mechanisms for early spinal cord vulnerability in CLN1 disease

Abstract: CLN1 disease is a fatal inherited neurodegenerative lysosomal storage disease of early childhood, caused by mutations in the CLN1 gene, which encodes the enzyme Palmitoyl protein thioesterase-1 (PPT-1). We recently found significant spinal pathology in Ppt1-deficient (Ppt1−/−) mice and human CLN1 disease that contributes to clinical outcome and precedes the onset of brain pathology. Here, we quantified this spinal pathology at 3 and 7 months of age revealing significant and progressive glial activation and vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
(148 reference statements)
1
12
0
Order By: Relevance
“…Nonetheless, several proteins altered in our transcriptomic analysis (LYZ2, TGM1, GPNMB, C4B, SERPINA3N, GFAP and C1QC) were confirmed to be increased in the proteomics analysis of CLN2 and were related to microglial and astrocytic function [ 32 ]. Interestingly, proteomic profiling of spinal cord in CLN1 disease (Ppt1 −/− model) identified canonical pathways consistent with the ones identified in this study for the Tpp1 −/− brains [ 96 ]; as well, notable regional differences were found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, several proteins altered in our transcriptomic analysis (LYZ2, TGM1, GPNMB, C4B, SERPINA3N, GFAP and C1QC) were confirmed to be increased in the proteomics analysis of CLN2 and were related to microglial and astrocytic function [ 32 ]. Interestingly, proteomic profiling of spinal cord in CLN1 disease (Ppt1 −/− model) identified canonical pathways consistent with the ones identified in this study for the Tpp1 −/− brains [ 96 ]; as well, notable regional differences were found in this study.…”
Section: Discussionsupporting
confidence: 85%
“…The secretion of cytokines and chemokines is of paramount importance for both astrocytes and microglia to exert pro- and anti-inflammatory effects on the process of neurodegeneration ( 93 ). The progressive elevation of multiple cytokines and chemokines has been confirmed by whole transcriptomics and/or proteomics in the forebrains and cerebella of Tpp 1 −/− mice ( 75 , 90 ) and forebrains and spinal cords of Ppt 1 −/− mice ( 68 , 94 , 95 ). Such evidence for the region- and subtype-specific nature of neuroinflammatory changes in CLN1 and CLN2 diseases correlates with the previously shown region- and subtype-specific immunoreactivity of astrogliosis and microglial activation markers.…”
Section: Glial Dysfunction In the Nclsmentioning
confidence: 85%
“…Moreover, the data obtained from the proteomic analysis can be used for dissecting the molecular targets and signaling pathways of a specific pathology. Previously, mass spectrometry (MS)-based proteomics protocols were applied to the investigation of different LSDs models such as CLN1 disease [12], Gaucher disease [13] and Fabry disease [14], leading to significant advances in the understanding of lysosomal function and pathology [15]. Specifically, OMICs analyses have been successfully used in a variety of studies to identify disease-related changes in NPCD.…”
Section: Of 15mentioning
confidence: 99%